SHAPING DEMOCRACY IN THE DIGITAL AGE: THE ROLE OF MEDIA IN INFLUENCING VOTER BEHAVIOR AND POLITICAL COMMUNICATION - Arditya Prayogi; Riki Nasrullah; Dimas Prasetya; Ryan Marina; Singgih Setiawan (LodDos Institute, 2024)
In the era of digital information disruption, media, both conventional and digital, significantly shapes political communication and voter behavior through agenda setting, framing, and information dissemination. This study aims to explore how media influences voters’ political perceptions and decisions, while addressing challenges and proposing solutions for effective political communication in the digital age. Employing a qualitative approach with a literature review method, this research analyzes data extracted from various credible sources, including scholarly articles and public media, using content analysis to derive new insights. The findings reveal that media directs public attention and shapes voter preferences, with social media amplifying participation but also exacerbating polarization and disinformation due to algorithmic biases and political buzzers. Media literacy emerges as crucial for fostering critical information analysis, alongside responsible media practices and ethical political campaigns. The study concludes that collaboration among media, politicians, academics, and civil society is essential to maintain journalistic integrity, enhance digital literacy, and ensure transparent regulations, fostering a healthy democratic ecosystem. By addressing these challenges, political communication can support informed voter decisions and strengthen democracy in the digital era.